CREATING A FAVORABLE ENVIRONMENT FOR ATTRACTING FOREIGN INVESTMENT AND STRENGTHENING ITS LEGAL FRAMEWORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the impact of foreign investment on the national economy of Uzbekistan, the creation of favorable conditions for attracting investments and doing business, strengthening the legal guarantees for the protection of the legitimate interests of entrepreneurs.